2011
DOI: 10.23939/chcht05.03.285
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Structure of Coal Organic Mass. 3. Dinamics of Coal Chemical Structure During Metamorphism

Abstract: Dynamics of coal chemical structure during metamorphism has been evaluated using mathematical model of metamorphism kinetics attached to the time axis in accordance with artificial coalification data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…In accordance with the existing conceptions [1], during natural coalification, which generates fuel chemical potential, gaseous and liquid products of metamorphism leave the "reaction zone", which is followed by the decrease of fixed residue mass and alteration of its elemental composition (mass contents of carbon ( q C ), hydrogen (q H ), oxygen (q O ), nitrogen (q N ), and sulphur (q S )) as a result of different reactions rates of the mentioned elements.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…In accordance with the existing conceptions [1], during natural coalification, which generates fuel chemical potential, gaseous and liquid products of metamorphism leave the "reaction zone", which is followed by the decrease of fixed residue mass and alteration of its elemental composition (mass contents of carbon ( q C ), hydrogen (q H ), oxygen (q O ), nitrogen (q N ), and sulphur (q S )) as a result of different reactions rates of the mentioned elements.…”
Section: Introductionsupporting
confidence: 72%
“…It is necessary to note the agreement between experimental data concerning elementary chemical structures and their molecular masses, which are given in [1] in the discussion of the "guest-master" model, as well as peculiarities of metamorphism interval near R 0 = 0.9 with the results of our model of artificial coalification. Thus, at n =22 the C n H 2n-28 O coincides with theoretically averaged structure C 22 H 16 O of the coal with R 0 = 0.9, characterized by equal mass contents of hydrogen and oxygen.…”
Section: Number Of Atomsmentioning
confidence: 53%
See 1 more Smart Citation
“…It is known that the reactions between carbon and CO 2 characterize the coke reactivity and proceed with appreciable endoeffect ( ∆ H = 189.1 kJ/mol). CO 2 conversion above 50 % is achieved at the temperatures higher than 1073 K [19][20][21][22][23]. That is why we observe the decrease of DTA curve at the temperatures higher than 1213-1233 K (Fig.…”
Section: Derivatographic Investigationsmentioning
confidence: 71%
“…In the works [1,2], an organic coal substance is represented as a collection of packets of condensed aromatic nucleus with side non-aromatic groups including oxygen, nitrogen, sulfur and other heteroatoms that chemically bind the neighboring packets to the spatial polymer. This view suggested that in the course of carbonization in lateral radicals, the carbon-oxygen bonds are replaced by carbon-carbon bonds [3].…”
Section: Introductionmentioning
confidence: 99%